1977
DOI: 10.1007/bf00199328
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Keyhole Limpet Hemocyanin (KLH) on the rat bladder

Abstract: Summary. Immunostimulation with agents such as BCG or K L H may represent an adjuvant therapy in treating patients with bladder cancer. To investigate the effects of direct instillation and injection of K L H into the bladder of sensitized and nonsensitized rats, K L H was injected Olsson et al. (1973) were able to show statistically significant immunologic reduction in the bladder cancer recurrence rate by immunizing patients with 5 mg K L H (keyhole limpet hemocyanin) intracutaneously. Attempts have also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The mechanism of immunostimulation by KLH includes an enhanced cytotoxic activity of effector lymphocytes towards neoplastic cells [9]. Klippel et al showed that a local injection of KLH into the bladder wall induced an infiltration of mononuclear immune cells [10]. The purpose of the present study was to evaluate the local response to instillation of intravesical KLH using an immunohistological analysis of the immunocompetent cells infiltrating the bladder wall.…”
mentioning
confidence: 91%
“…The mechanism of immunostimulation by KLH includes an enhanced cytotoxic activity of effector lymphocytes towards neoplastic cells [9]. Klippel et al showed that a local injection of KLH into the bladder wall induced an infiltration of mononuclear immune cells [10]. The purpose of the present study was to evaluate the local response to instillation of intravesical KLH using an immunohistological analysis of the immunocompetent cells infiltrating the bladder wall.…”
mentioning
confidence: 91%
“…This stimulato ry effect has been involved in the induction of effector lymphocytes against neoplastic cells [9], Klippel et al [10] demonstrated this by locally injecting KLH into the blad der thereby inducing a mononuclear cell infiltration. We have recently shown that the intravesical instillation of KLH into patients with superficial transitional cell carci noma (TCC) is also associated with marked lymphocyte and macrophage infiltration of the bladder mucosa and submucosa [11,12].…”
Section: Introductionmentioning
confidence: 99%